Best Practices for Controlled Ovarian Stimulation in In Vitro Fertilization - Jungheim, Emily S.; Meyer, Melissa F.; Broughton, Darcy E. (Seminars in Reproductive Medicine, 2015)
As applications for IVF have expanded over the years, so too have approaches to controlled ovarian stimulation (COS) for IVF. With this expansion and improved knowledge of basic reproductive biology, there is increasing interest in how COS practice influences IVF outcomes, and whether or not specific treatment scenarios call for personalized approaches to COS. For the majority of women undergoing COS and their treating physicians, the goal is to achieve a healthy live birth through IVF in a fresh cycle. Opinions on how COS strategy best leads to this common goal varies among centers as many clinicians base COS strategy not on evidence obtained through prospective randomized trials, but rather through observational studies and experience. Overall, when it comes to COS most clinicians recognize the approach should not be “one size fits all,” but rather a patient-centered approach that takes the existing evidence into consideration. We outline the existing evidence for best practices in COS for IVF, highlighting how these practices may be incorporated into a patient-centered approach.
Keywords: controlled ovarian stimulation; gonadotropins; in vitro fertilization